PLCε1 suppresses tumor growth by regulating murine T cell mobilization. (9th January 2020) - Strazza, M; Adam, K; Smrcka, A V; Lerrer, S; Mor, A
Summary: Phospholipase C epsilon 1 (PLCε1) is a unique member of the phospholipase family, in that it also functions as a guanine nucleotide exchange factor (GEF) for the small GTPase Rap1. It is this function as a Rap1 GEF that gives PLCε1 an essential role in chemokine-mediated T cell adhesion. We have utilized a syngeneic tumor model, MC38 cells in C57BL/6 mice, and observed that tumors grow larger and more quickly in the absence of PLCε1. Single-cell analysis revealed an increased CD4 + /CD8 + ratio in the spleens, lymph nodes and tumors of PLCε1 knock-out tumor-bearing mice. T cells isolated from PLCε1 knock-out mice were less activated by multiple phenotypical parameters than those from wild-type mice. We additionally noted a decrease in expression of the chemokine receptors C-X-C chemokine receptor type 4 (CXCR4) and C-C motif chemokine receptor 4 (CCR4) on CD4 + T cells from the spleens, lymph nodes and tumors of PLCε1 knock-out mice compared to wild-type mice, and diminished migration of PLCε1-depleted CD3 + T cells towards stromal cell-derived factor (SDF)-1α. Based on these results, we conclude that PLCε1 is a potential regulator of tumor-infiltrating lymphocytes, functioning, at least in part, at the level of T cell trafficking and recruitment. Graphical Abstract: